Introducción y multiplicación in vitrodel cultivo de ajo variedad Morado Barranquino - Carhuaricra E., Karina (2012)
We determine the effect of modified culture medium using different growth regulators concentrations (auxins / cytokinins) for regeneration and propagation of in vitro garlic plants (Allium sativumL.) var. ‘Morado Barrran-quino’. In the introduction stage meristem tips were cultured in test tubes up to regeneration. It was determined that medium MSM + IBA 0.6 mg/L was most suitable for the meristem tip differentiation and development. 13 weeks old microplants obtained on introduction stage were used for multiplication, obtaining the formation of a cluster after each subcultive. The best multiplication ratio was obtained in MMA medium + IAA 2.5 mg/L + KIN 5.0 mg/L and MSM medium + 2iP 1.5 mg/L with 4.71 and 4.79 respectively.